Synthesis and Characterization of A Polynuclear Yttrium Trifluoroethoxide and Its Activity for Oligomerization of Phenyl Isocyanate - 彭红梅 姚英明 邓明宇 张勇 沈琪 (Journal of rare earths, 2006)
A polynuclear yttrium trifluoroethoxide was synthesized and its activity for the oligomerization of phenyl isocyanate was tested. Reaction of anhydrous YC13 with CF3CH2ONa in a 1 ： 3 molar ratio in THF at room temperature, after workup, gave complex 1 as colorless crystals. The composition of complex 1 is [Y（OCH2CF3）3]6ONa2（THF）12, which was identified by elemental analysis and ^1H NMR. Further X-ray structure determination reveals that complex 1 is a polynuclear ion pair compound, [Y6（μ6-O）（OCH2CF3）18]^2- [Na（THF）6]2＋ （1）. The crystal data of complex 1 are trigonal, P-3 space group, a = 1.78440（14） nm, b = 1.78440（14） nm, c = 1.27395（12） nm, γ= 120°, V=3.5129（5） nm^3, Z = 1, Dc = 1.607 mg·m^-3, μ = 2.591 mm^- 1（Mo Ka）, F（000） = 1710, R = 0.067, wR = 0. 182. Preliminary results demonstrated that complex 1 is a highly effective catalyst for the oligomerization of phenyl isocyanate.